Development of Biology Module Based on Metacognition on Coordination System Materials With Concept Maps For Students Class XI SMA/MA - Riva Yola Yuanda; Ristiono Ristiono; Muhyiatul Fadilah (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2017)
The purpose of this research is to result and show the validity and practicality of biology module about coordination system material based on metacognition with concept map for students in Senior High School. Type of research is research and development. This research applies 3 steps from 4D model, that are define, design, and develop. The subject of this research are 5 experts as validator, 3 teachers, and 49 students classes XI of SMAN 2 Padang. Data gained is categorized into primary data, as it is collected from validity and practicality questionnaire which is directly filled by research subjects. The data was analyzed descriptively. The result of validity is 88,5% in criteria valid, practicality by teachers is 90,4% in criteria very practice, and practicality by students is 85,8% in criteria practice. It can be concluded that the Biology Module on coordination system material based on metacognition with concept map for students in Senior High School is valid and practical.